HUBUNGAN TINGKAT KECERDASAN SPIRITUAL DENGAN MEKANISME KOPING PADA REMAJA DI SMAN 2 PURWOKERTO - Martyarini Budi Setyawati; Indri Heri Susanti (Universitas Harapan Bangsa Purwokerto, 2013)
Status of work is an attempt to change a person's income so that the needs aremet. In women who have a high activity or low income mothers so that motherscan not allocate income to meet the nutritional intake of children aged 6-24months with the well so that it can predispose a mother who has good knowledgebut has stunting.The purpose of this study was to determine differences in the nutritional status ofchildren aged 6-24 months between working mothers and the mother does notwork. The research method uses analytic observation with a sampling technique issimple random sampling conducted by cross sectional. Number samples are 71respondents. How is the data collection observation and interviews.Data analysis used contingency correlation coefficient t. Results of researchmengggunakan contingency coefficient t which shows the difference nutritionalstatus of children aged 6-24 months with working mothers and Differencesnutritional status of children aged 6-24 months with the mother does not work.based on the level of significance (approx. Sig.) 0237 values obtained over thecriteria of significance of 0.05. Based on the results of the analysis, it is deducedthat the relationship between the two variables no significance or no difference inthe nutritional status of children 6-24 months between working mothers andmothers do not workKeywords: Nutritional Status, Toddler, Mother's Employment Status